Assessing farm-level sustainability: a comparative analysis of horticultural production systems in Eritrea - Haile, Bereket T.; Dougill, Andrew J.; Ramoelo, Abel; Kidane, Tesfai T. (Frontiers in Sustainable Food Systems, 2025)
IntroductionMeasuring the sustainability of agricultural practices at the farm level is a prerequisite for devising effective policies and strategies. This study offers an in-depth farm-level sustainability assessment of Eritrea's horticultural sector. It aims to assess the sustainability of horticultural crop production using 12 customized indicators co-developed with local stakeholders, identify the principal factors influencing sustainability performance, and compare the sustainability performances across two regions of Eritrea with different agroecological and socioeconomic settings.MethodsPrimary data from 170 horticultural farmers were collected using a field survey focusing on activities conducted from 2020 to 2022. The assessment uses a traffic light approach to classify farms into three categories: unsustainable (red), acceptable (yellow), and sustainable (green). Multiple Linear Regression (MLR) is applied to explain the main factors contributing to the sustainability score of farms across the studied regions.ResultsThe study shows disparities in sustainability performance between the two study regions as measured by the indicators. The MLR model shows that farming experience, extension services, and cooperative membership significantly influence most sustainability outcomes (p < 0.05).DiscussionThis study highlights the necessity for a context-specific approach to assess farm-level sustainability. By mapping the sustainability landscape of the horticultural sector and identifying key levers for improvement, the study paves the way for informed, impactful strategies to advance agricultural sustainability at the farm level.